Estrutura genética e demográfica do caranguejo-uçá (Ucides cordatus) na costa do Brasil - Vianna, Lucas Alves (2013)
The crabspeciesUcides cordatus, commonly knowninBrazil as caranguejo-uçá,is found in mangroves from the state of Santa Catarina, in Brazil,to Florida,in United States. In Brazil, the food industry demand on this species isthe cause of the fishing of several tons of specimens eachyear. Moreover, the mangrove destructions and the originof a lethal disease are other causes of severe decreasein natural stocks of U. cordatus. Since population reductions can produce bottleneck effects and, consequently, fitness reduction in specimens over time, population genetics studies that aimto understand the pattern of genetic distribution among populations, calculate the gene flow and evaluate the demographic trends are criticalinthe creation of management and conservation programs. Thus, here we used 568 bp sequences of the subunit 1 of the mitochondrial gene cytochromec oxidase of 181 U. cordatusspecimens,collected in 15 localities over the Brazilian coast, among the states of Santa Catarina and Maranhão, which comprises almost the whole occurrence zone of this species in Brazil. From all sequences, 80 haplotypes were found, showing a high haplotypediversity (h=0,925).On the other hand, the nucleotidediversity was very low (p =0,00462), what is explained by the few base pairs differences among the haplotypes. The hierarchical relationship among the haplotypes did not reveal any sign of geographicstructure of the genetic diversity. Besides, the analysis of molecular variance and the F-statistics values (Fst=0,00231) revealed that major genetic divergence in U. cordatusis foundin the intrapopulationlevel (98,8%), and only a minor amount of this divergence (2,5%) is due the differences among the groups of populations. The Fu’s Fs and Tajima’s D results were negative and indicate that the U. cordatuspopulations expanded recently.This scenario was also confirmed by the mismatch distribution analysis, in which unimodal distributions were found for all populations. Hence, our data are consistent withprevious works that indicate that the gene flow in U. cordatuspopulations is enough to produce genetic homogeneityamong them. This profile is also compatible with thestrategy of larval exportation to open sea in this species, where many oceanographic agents, such as marine currents, can act in a way to amplify the larval dispersion